2023
DOI: 10.1093/toxres/tfad034
|View full text |Cite
|
Sign up to set email alerts
|

The ameliorative effects of quercetin and curcumin against subacute nephrotoxicity of fipronil induced in Wistar rats

Abstract: Fipronil is a phenylpyrazole insecticide that is widely used in agricultural, veterinary, and public health fields for controlling a wide variety of insect species and it is an environmentally potent toxic substance. Curcumin and quercetin, which are well-known natural antioxidants, are widely used to prevent the harmful effects of free radicals on biological systems. The present study aimed to determine the potential ameliorative effects of quercetin and/or curcumin on fipronil-induced nephrotoxicity in rats.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 64 publications
1
1
0
Order By: Relevance
“…Similar histopathological alterations in liver tissue were also reported by other researchers following xenobiotic. 44 , 58 , 59 Toxicity studies with NiO microparticles and NPs in liver tissue have been done in the past and the results are similar to the current study. 4 , 5 , 6 , 9 …”
Section: Discussionsupporting
confidence: 85%
“…Similar histopathological alterations in liver tissue were also reported by other researchers following xenobiotic. 44 , 58 , 59 Toxicity studies with NiO microparticles and NPs in liver tissue have been done in the past and the results are similar to the current study. 4 , 5 , 6 , 9 …”
Section: Discussionsupporting
confidence: 85%
“…Reactive oxygen species (ROS) are known to be responsible for damages in kidney and liver tissues. Some researchers have suggested that ROS are associated with insecticide use, and it has been reported that the increase of MDA levels in hepatic tissue indicates the injury of biological membranes caused by excessive ROS accumulation (Uzunhisarcıklı et al 2021). Oxidative stress has been the focus of research as a possible mechanism of environmental pollutions toxicity (Zhou et al 2011).…”
Section: Introductionmentioning
confidence: 99%